F04 Selisistat: potential pharmacodynamic readouts based on transcriptomics. (29th August 2012) - Westerberg, G; Diamanti, D; Pollio, G; Mori, E; Fondelli, C; Morena, E; Magnoni, L; Tarditi, A; Malusa, F; Tabrizi, SJ; Landwehrmeyer, B; Caricasole, A; et al.
Abstract : Background: Siena Biotech SpA is developing selisistat (SEN0014196) as a potentially disease-modifying therapy for HD. Selisistat is a potent and selective SirT1 inhibitor (IC50 98 nM) that has shown benefit across a range of preclinical models for HD, from cells and neurons transfected with mutant huntingtin to transgenic Drosophila and R6/2 mice. The compound has shown to be safe and well tolerated in healthy volunteers and with a favourable pharmacokinetic profile. Transcriptional modulation mediated by SirT1 through deacetylation of transcriptional factors should be modulated by selisistat, thus generating a compound-specific gene expression profile. Aim: To investigate the gene expression modulation of selisistat in whole blood derived from HD patients in a Phase 1B study and employ these transcriptional effects as a candidate pharmacodynamic readout for the compound. Methods: By crossing results obtained from a microarray study performed on blood samples of healthy volunteers treated with a single dose of selisistat (Phase 1) and from investigation of different literature hypotheses, a candidate transcriptional signature for the compound, comprised of 10 genes, has been identified and validated by real-time PCR (RT-qPCR) in blood samples of healthy subjects treated with multiple doses of selisistat during Phase 1. This candidate signature has been investigated by RT-qPCR in total RNA isolated from whole blood derived from HD patients treated with selisistat or placebo and collected at different time points during the Phase Ib study. Results and Conclusions: The effects of selisistat on gene expression from blood samples from a 14-day Phase1b study in HD patients at two dose levels of selisistat and placebo will be presented.